Haemoglobin measurement by point-of-care devices- a need of the hour: study conducted on antenatal females - Kumar, Aman; Arora, Sheetal; Sethi, Surabhi; Ranga, Sunil (International Journal of Research in Medical Sciences, 2022)
Background: Haemoglobin measurement in antenatal care can help in timely detection and treatment of anaemia, which is a major contributory factor to maternal mortality in developing countries. The transport of samples for haemoglobin assessment may delay the treatment, resulting in preventable deaths. Haemoglobin measurement by point of care testing (POCT) devices is easy, quick and less invasive. There are very few studies which compare the capillary blood haemoglobin using point of care devices with venous blood samples. This study was conducted to compare capillary blood haemoglobin using POCT device with venous blood haemoglobin using haematology analysers in antenatal Indian females. Methods: One hundred pregnant women were recruited during their first trimester antenatal visits. Hemoglobin by finger prick capillary sample (POCT) was compared with haemoglobin of venous sample analysed by the haematology analyser (Beckman coulter) which was considered as gold standard. Intraclass correlation co-efficient based on Bland Altman analysis was computed using SPSS v21. A p value less than 0.05 was considered statistically significant. Results: The intraclass correlation coefficient of 0.97 was recorded with central laboratory reference standard, with a mean difference of -0.481 gm% and -0.482 gm% by capillary and venous blood samples, respectively (p<0.0001). Conclusions: A good agreement between capillary blood haemoglobin (POCT device) and venous blood (haematology analyser) was achieved.